Training residents in minimally invasive surgery; confirming competence or hoping for the best?. (30th July 2022) - Fransson, Boel A.
Abstract: Background: Veterinary minimally invasive surgery (MIS) is rapidly developing, and most surgeons are performing MIS in their clinical practice. The technical skills of presented surgical techniques are increasingly complex. Required training of American College of Veterinary Surgeons (ACVS) surgical residents in soft tissue MIS (laparoscopy/thoracoscopy) are limited to traditional apprentice training. Unfortunately, such training has been found insufficient to create competent MIS surgeons. Aim of the review: This review discusses development of MIS training for Doctor of Medicine (M.D.) residents in context of veterinary applicability and investigates comparative evidence for how to best train veterinary residents in soft tissue MIS. Conclusions: A structured curriculum, with validated tasks and clear training goals have been found imperative for training success. Such a curriculum includes both didactic sessions and manual skills training, with video tutorials and reading material to inform and motivate the residents. Implications of key findings: ACVS residents and diplomates may benefit if a MIS curriculum was developed and made available to all training programs.